Nuclear Insulin-Like Growth Factor Binding Protein-3 As a Biomarker in Triple-Negative Breast Cancer Xenograft Tumors: Effect of Targeted Therapy and Comparison With Chemotherapy - Julovi, Sohel M.; Martin, Janet L.; Baxter, Robert C. (Frontiers in Endocrinology, 2018)
Triple-negative breast cancer (TNBC) typically has a worse outcome than other breast cancer subtypes, in part owing to a lack of approved therapeutic targets or prognostic markers. We have previously described an oncogenic pathway in basal-like TNBC cells, initiated by insulin-like growth factor binding protein-3 (IGFBP-3), in which the epidermal growth factor receptor (EGFR) is transactivated by sphingosine-1-phosphate (S1P) resulting from sphingosine kinase (SphK)-1 activation. Oncogenic IGFBP-3 signaling can be targeted by combination treatment with the S1P receptor modulator and SphK inhibitor, fingolimod, and the EGFR kinase inhibitor, gefitinib (F+G). However, the interaction of this treatment with chemotherapy has not been documented. Since we observed nuclear localization of IGFBP-3 in some TNBC tumors, this study aimed to evaluate the prognostic significance of nuclear IGFBP-3 in preclinical models of basal-like TNBC treated with F+G and doxorubicin. Orthotopic xenograft tumors were grown in nude mice from the human basal-like TNBC cell lines MDA-MB-468 and HCC1806, and were treated with gefitinib, 25 mg/Kg, plus fingolimod, 5 mg/Kg, 3-times weekly. In some studies doxorubicin was also administered once-weekly for 6 weeks. Tumor tissue proteins were quantitated by immunohistochemistry (IHC). Interaction between doxorubicin and F+G was also studied in proliferation assays in vitro. In both tumor models, tissue staining for IGFBP-3 was predominantly nuclear. Combination F+G significantly enhanced mouse survival, decreased nuclear IGFBP-3 and Ki67 staining, and increased apoptosis (cleaved caspase-3) staining. Kaplan-Meier survival analysis showed that a high tumor IGFBP-3 IHC score (>median), like a high Ki67 score, was significantly associated with shorter survival time, whereas a high apoptosis score was associated with prolonged survival. Studied in vitro in both cell lines, low-dose doxorubicin, that had little effect alone, strongly enhanced the cytostatic effect of low-dose F+G combination. However, in both in vivo models, doxorubicin at maximum tolerated dose neither inhibited tumor growth when administered alone, nor enhanced the significant inhibitory effect of F+G. We conclude that doxorubicin may not add benefit to the inhibitory effect of F+G unless its dose-limiting toxicity can be overcome. Nuclear IGFBP-3 appears to have potential as a prognostic marker in TNBC and could be evaluated for clinical utility.